Socio-economic nature of proper taxes in state budget revenues and their role in the tax system (Eurasian Research Bulletin, 2023)
This article is aimed at ensuring the effectiveness of the tax and budget system in the new development strategy in the country. Formulas for calculating tax potential are also presented, as well as suggestions for improving tax policy, improving the development of existing innovative methods and methodological approaches in determining the needs of the budget and key aspects of equalization programs, the use of comprehensive methods of economic and mathematical modeling and forecasting